Exploring the effects of position-related information on the perception of scenario-based passing opportunities: An information integration theoretical approach - Steiner, S.; Köstinger, C. (Current Issues in Sport Science, 2020)
When football players are preparing to pass the ball, they consider contextual information provided by the current game situation to identify passing opportunities and choose the one that appears most beneficial. In the search for contextual information indicating such opportunities, a recent study analyzing the relationships between the position-related characteristics of game situations and athletes` passing behavior reports that athletes generally prioritize passing options based on their team members` areal proximity, the openness of the passing lanes leading to team members, and how closely the team members are covered by the opponents. While the found relationships indicate the positional features` relevance to the athletes` passing behavior, the importance of single bits of positional information and their integration into subjectively perceived passing opportunities remain unknown. The aim of this study is to begin closing this gap and analyze how multiple athletes weigh and integrate position-related information within their subjective process of perceiving passing opportunities. The study uses a 3x3x3 within-subject design. Twenty-one football players provided information about the perceived quality of passing opportunities within standardized game scenarios. The data were analyzed using an information integration theoretical approach combined with mixed linear modeling. The results reveal substantial interpersonal differences regarding the importance players attribute to specific positional information and how they integrate the positional information. Two recurring patterns of information integration were found. In most of the cases, the results indicate additive information integration. However, in some cases, the results indicate that players deviate from additive information integration when a single piece of positional information seemingly dominates the athletes` perceptions. In the future, IIT approaches can be adopted to research designs using virtual reality, including other sets and ranges of contextual information, as well as other sports and sports situations in which the integration of information into subjective perceptions is of interest.